ChemInform Abstract: Gold Carbenes, Gold‐Stabilized Carbocations, and Cationic Intermediates Relevant to Gold‐Catalyzed Enyne Cycloaddition. Issue 41 (September 2016) - Harris, R. J.; Widenhoefer, R. A.
Abstract: Review: [77 refs.